Elementos [re]construtivos do círculo da paz em contexto escolar - Oliveira, Fátima Aparecida Militz de (2018)
This dissertation is part of the Master's Degree in Public Policies and Educational Management, research line 2 - Pedagogical Management and Educational Contexts, Federal University of Santa Maria (UFSM-RS). Throughout the professional trajectory, I developed my activities in an interdisciplinary and transdisciplinary way, integrating health, education and assistance of the student and their families. It is presented as a research question: Is it possible to resign the Circle of Peace from the personal and professional trajectory, in the different educational contexts? Consistent with this problematization, it seeks to elucidate it through the general objective of ‘remeaning the Circle of Peacebuilding from the knowledge and actions of interventions in the different educational contexts’ and as specific objectives: to promote the construction and reconstruction of links in the circles of peace; to provide activities that develop self, hetero and interknowledge in an experience, promoting sensitivity, harmony and learning of human values; These objectives guide the work developed in Peace building Circles to propose new possibilities for resignification in the school context, from where school-family integration demands and converges. The theoretical support that supports the argument is Bronfenbrenner's Bioecological Theory of Human Development (1992,1995,1999). The methodological contribution stems from the autobiographical narrative, from Marinas (2004,2007,2014) Abrahão (2014) and Marquezan (2015), in which the researcher gives new meanings to the lived as mediator in Circles of Peace Building, putting in evidence the interaction in a context of approach between school and family. Circularity thinking, proposed by Morin (2011), allowed the punctuation of reconstitutive elements of the Peace Building Circle as a materiality of the investigative process and of this master's thesis. The Reframed Peacebuilding Circle rescues the "attentive look and sensitive listening" of being in various dimensions and points to a new learning, how to deal with emotions and rebuilding bonds as possible paths to the balance of being.